Pembuatan Spray Herba Serai Wangi (Cymbopogon nardus L) Sebagai Anti Nyamuk Culex s.p - Taufiq Taufiq; Husnul Khatimah (Parapemikir : Jurnal Ilmiah Farmasi, 2023)
Lemongrass plants herbs is known as the scent and it has fragrant and invigorating , also has a volatile oil content . The womb on oil volatile lemongrass wangi ( Cymbopogon nardus L ) there are three components namely sitronelal , sitronelol and geraniol that has the potential as an insecticide vegetable ( repellent mosquito ). The purpose of this research is to produce preparation spray leaves and stems lemongrass wangi ( Cymbopogon nardus L ) as anti mosquito culex s.p . Spray used to the way sprayed without direct contact with the hand so that the contamination microorganism more low . Spray herbaceous lemongrass fragrant ( Cymbopogon nardus L ) made into 4 formulation with the f0 0 %  individually concentration , f1 % 10 , f2 % 15 , 20 % f3 . The stability physics spray herbaceous fragrant cymbopogon nardus lemongrass ( i ), covering the organoleptik the ph of refuse and the mosquito. The evaluation results f0 test ph , formula one , f2 , f3 order is 5 .The results of the power turning mosquito shows that power turning more effective where the f3 with a capacity of turning of 69,07 % . This proved that spray a volatile oil of citronella fragrant ( Cymbopogon nardus L )) can be used as repellent.